DNA Patchy Particles. (3rd April 2013) - Feng, Lang; Dreyfus, Rémi; Sha, Ruojie; Seeman, Nadrian C.; Chaikin, Paul M.
<x xml:space="preserve">Abstract</x> A simple and effective way to make DNA patchy particles is reported. A small patch of DNA strands is "stamped" from a gold surface onto colloidal particles of different sizes by streptavidin‐biotin bonds. These DNA patchy particles provide direction‐selective and thermoreversible interactions, and hence can lead to unique assembly protocols and structures controlled by temperature. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>